Assembly and electrochemistry of carbon nanomaterials at the liquid-liquid interface. (10th June 2019) - Rodgers, Andrew N.J.; Rabiu, Aminu K.; Toth, Peter S.; Adams, Ralph W.; Dryfe, Robert A.W.
Abstract: The interfacial adsorption of single-walled carbon nanotubes and few-layer graphene flakes, prepared by solution phase exfoliation, is compared. Strong adsorption of carbon nanotubes was observed at the water/1, 2-dichloroethane interface, while a weaker adsorption of the graphene dispersion was seen. Addition of electrolyte to the organic phase was found to have a strong effect on the adsorption of graphene. A simple surface energy model does not fully explain these observations, rather residual charges and their distribution appears to be the key factor behind this difference in adsorptive behaviour. Carbon nanomaterials adsorbed at the liquid-liquid interface can function as bipolar electrodes: a preliminary investigation of the oxidation of the 1, 2-dichlorobenzene by metal-modified graphene particles is performed.